ANALYSIS OF STUDENTS’ WRITING BY USING SURFACE TAXONOMY STRATEGY AT PRE-PLANET PROGRAM OF KRESNA ENGLISH LANGUAGE INSTITUTE - Ramadhani, Anisah (FKIP UNISKA, 2020)
Considering the importance of grammatical aspect in the writing process, the students should have gramatical knowledge since they are as a beginner. This research aims at error analysis of students’ writing by using surface taxonomy strategy and the factors happen in error of students’ writing based on surface taxonomy strategy at Pre-Planet Program of Kresna English Language. The research study is classified into qualitative research. The instrument that the researcher used are document and interview. By analyzing the students’ answer sheet, the writer obtained their scores of the test result and found that the highest error was found in Misinformation, the students committed 147 times or 68.37% out of the whole errors. The second is Omission, from the data that was found 37 times or 17.21 % out of the whole errors of omission. Then, Addition was found 27 errors or 12.56 % on their writing. The lowest percentage is Mis ordering, was found 4 times or 1.86% errors. The factors of those errors because of the students do not know well about how to use the structure of sentence, the vocabulary that the students do not know before even how to spell it. Writing can begin from a simple piece to a more advanced level of writing. It includes the organization of words, phrases, clauses and sentences.